PENGARUH PEMBELAJARAN KATEKISASI SIDI DAN POLA ASUH ORANGTUA TERHADAP KARAKTER KRISTIANI PEMUDA DI HKBP SE-RESSORT SIPOHOLON-1 KABUPATEN TAPANULI UTARA TAHUN 2025 - Dody Kasih Napitupulu; Andar Gunawan Pasaribu; Rencan Carisma Marbun (STKIP Subang, 2026)
The objectives of this study were: (1) to determine the positive and significant effect of Sidi catechism instruction on the Christian character of youth in HKBP churches throughout Ressort Sipoholon-1; (2) to determine the positive and significant effect of parenting styles on the Christian character of youth in HKBP churches throughout Ressort Sipoholon-1; and (3) to determine the positive and significant effect of Sidi catechism instruction and parenting styles simultaneously on the Christian character of youth in HKBP churches throughout Ressort Sipoholon-1. This study employed an inferential quantitative research method. The population consisted of all youth members of HKBP churches throughout Ressort Sipoholon-1, North Tapanuli Regency, totaling 102 individuals, from which a sample of 51 respondents was selected. The research instrument was tested on 30 HKBP youth (Naposo Bulung) in Ressort Sipoholon-1, and the results indicated that all research instruments were valid and reliable. Data were collected using a closed-ended questionnaire consisting of 72 items.The results of the data analysis revealed that: (1) the calculated F-value was greater than the F-table value (24.308 > 3.23), indicating that Sidi catechism instruction had a positive and significant effect on the Christian character of youth in HKBP churches throughout Ressort Sipoholon-1. The contribution of this effect was 33.2%; (2) the calculated F-value was greater than the F-table value (31.097 > 3.23), indicating that parenting styles had a positive and significant effect on the Christian character of youth in HKBP churches throughout Ressort Sipoholon-1. The contribution of this effect was 38.8%; and (3) the calculated F-value was greater than the F-table value (19.941 > 3.23), indicating that Sidi catechism instruction and parenting styles simultaneously had a positive and significant effect on the Christian character of youth in HKBP churches throughout Ressort Sipoholon-1. The combined contribution of these variables was 45.4%. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (H₀) was rejected.